Conflict Around Cural Land Ownership in Nagari Simpang Tiga and Kinali Regency West Pasaman (1996-2024) - Wangi, Annisa Wiediapandan; Naldi, Hendra (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This research examines the ulayat land conflict in Nagari Kinali and Nagari Simpang Tiga from 1996 to 2024. The main issues discussed are the roots of the ulayat land ownership conflict, the period of the conflict, and its resolution. The research uses historical methods with four stages: heuristics, source criticism, interpretation, and historiography. Data was collected from various primary and secondary sources, including personal documents, archives, and interviews with traditional leaders and community members. Secondary sources include books, journals, theses, and newspapers. The research results show that the conflicts in Kinali and Simpang Tiga were caused by investors who did not fulfill their agreements with ninik mamak, such as not establishing plasma plantations. Conflict resolution is carried out through traditional deliberations and legal channels, but the court has not yet given a decision that the ninik mamak considers fair. This conflict still continues today with the dispute unresolved.